Nannofossil records from sediment core SHAK06-5K - Ausín, Blanca; Hodell, David A; Cutmore, Anna; Eglinton, Timothy Ian (PANGAEA, 2019)
Nannofossil relative abundances (%), nannofossil accumulation rates (NAR) and N ratio for the last 28 kyr from core SHAK06-5K from the SW Iberian margin.
Keywords: Coccoliths; Iberian margin; last deglaciation; nannofossil; Upwelling